IMPACT OF PERSONALIZATION ON ONLINE SHOPPING INTENT: THE MEDIATING ROLE OF PERCEIVED AD INTRUSIVENESS - Jelčić, Sandra; Čule Karačić, Nikolina; Mabić, Mirela (Economic Review: Journal of Economics and Business, 2025)
Due to rapid technological and Internet advancements, online shopping has become more popular, widespread, convenient, and easier for consumers. Common advantages of online shopping include convenience, product and service variety, price comparison, ability to view online customer reviews, possibility of different payment methods, accessibility, etc. However, it is important to consider potential challenges related to online shopping, such as inability to physically inspect the product before purchase, concerns about security and privacy, and exposure to fraud or counterfeit goods. The above factors emphasize the importance of ongoing research into the characteristics of online shopping because, with technological advances, online shopping is becoming increasingly present in everyday life. Purchase intention is one of the fundamental predictors of future consumer behavior. Personalized offering is one of the factors that influence online shopping intention. However, a consumer’s experience of personalized ads can positively and negatively affect their perception of intrusiveness. Perceived intrusiveness of displayed ads can significantly impact their online purchase intention. This study investigates how the perceived personalization of online ads affects online purchase intention, with a focus on the mediating role of perceived intrusiveness. Theoretical contributions include insights into the interplay between personalization, intrusiveness, and purchase behavior, while practical implications guide marketers in mitigating the negative effects of personalized advertising.